Pemberdayaan Masyarakat Berbasis Partisipasi Lokal melalui Pengelolaan Desa Wisata di Desa Panglipuran, Bali untuk Mendukung Kemandirian Ekonomi - Hilmi Nur Huda Al Mubaroq; Nihayatus Sholichah; Widyawati (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Panglipuran Village, Bali, is one of the traditional tourism villages with significant potential to support the economic independence of local communities. However, community empowerment in this village faces various challenges, such as limited resources, a lack of community capacity in management, and dependence on external parties. This study aims to analyze community empowerment based on local participation through the management of the tourism village, using the community empowerment theory proposed by Jim Ife. The study emphasizes the importance of resource, opportunity, knowledge, and skill indicators in supporting the success of community empowerment. This research employs a qualitative descriptive method, collecting data through in-depth interviews, field observations, and documentation. The primary informants of the study include community leaders, local business actors, and tourism village managers. The findings reveal that empowerment through resource indicators has increased the income of craft businesses by 150%, from IDR 2 million to IDR 5 million per month. Furthermore, the opportunity indicator successfully opened avenues for the community to manage homestays, increasing income by up to 70% compared to previous levels. The knowledge and skill indicators also proved significant, with more than 90% of the community actively participating in training, which supports the sustainable economy of the tourism village. The conclusion of this study highlights that community empowerment based on local participation has a positive impact on the economic independence of the Panglipuran Village community. The novelty of this research lies in the integration of community empowerment elements with local wisdom values, such as mutual cooperation and cultural preservation. This model contributes not only to economic development but also serves as a best practice example in sustainable local participation-based tourism village management.